The set-based concurrent engineering application: a process of identifying the potential benefits in the surface jet pump case study - Mohd Maulana, Muhd Ikmal I. Bin; Al-Ashaab, Ahmed; Flisiak, Jakub W.; Araci, Zehra Canan; Lasisz, Piotr W.; Shehab, Essam; Beg, Najam; Rehman, Abdullah (Elsevier, 2017)
The Set-Based Concurrent Engineering (SBCE) is the methodology that can improve the efficiencies and effectiveness of product development. It is found that the SBCE approach provided a suitable knowledge environment to support decision making throughout the development process. This paper presents the potential tangible benefits gained from the application of the SBCE in an industrial case study of a Surface Jet Pump (SJP) that is used to revive the production of oil/gas from the dead wells. The well-structured SBCE process model and the process of identifying the potential benefits proposed in this paper will clarify the gap in the development of the SBCE in the company. The potential tangible benefits are established in a few key areas such as product innovation, product performance, manufacturing cost, and project success rate.
Keywords: lean product development; set-based concurrent engineering; trade-off curves; creating knowledge; visual knowledge; oil and gas production; surface jet pump